Seafloor pockmarks and gas seepages, northwestern Bay of Fundy, New Brunswick, Canada - Broster, Bruce E.; Legere, Christine L. (Atlantic Geoscience, 2018)
Bathymetric images of linear and circular pockmark depressions on the Bay of Fundy seafloor, offshore eastern Canada, are interpreted to have been caused by escaping gas from underlying sediment or bedrock. Shallow interstitial gas within marine sediments restricts seismic reflection imaging (acoustic masking) of sub-bottom units resulting in obscured reflections within seismic profiles, confirming that interstitial gas is present in the underlying units. Pockmark fields are frequent in several bays and shallow coastal areas along the northern coast of the Bay of Fundy. The largest field containing over 10 000 pockmarks occurs in Passamaquoddy Bay, an estuary underlain by igneous and metamorphic bedrock. These features are interpreted to be caused by generation of biogenic methane from the microbial breakdown of organic matter buried within Holocene-age sediments and along the underlying Pleistocene/Holocene unconformity. The unconformity is recorded as a distinctive horizon that represents a time when glacier recession resulted in exposure of parts of the bay to sub-aerial erosion and growth of terrestrial vegetation at locations subsequently submerged by post-glacial transgression. Three areas of potential thermogenic gas occurrence were identified in seismic profiles collected south and east of The Wolves islands, New Brunswick. The underlying bedrock has not yet been precisely mapped, although outliers of Carboniferous-age bedrock that is the major petroleum source in New Brunswick may extend into this area of the Bay of Fundy.